High-heat-resistance laser repair method for failed mold
By introducing nano-TiC+TiB2 particles into die-casting molds and using laser additive technology, the problem of mold failure due to thermal fatigue and wear is solved, performance recovery or overtake is achieved, mold life is extended and resources and costs are saved.
Patent Information
- Application Number
- CN202411986479.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-21
AI Technical Summary
Die-casting molds are prone to failure due to thermal fatigue and wear in harsh working environments, and it is difficult for the prior art to effectively repair or restore their performance.
The intermediate alloy method is used to introduce nano-TiC+TiB2 particles into the steel of the scrap mold, and repair it at the damaged parts through laser additive technology to form nano-particle reinforced mold wire material.
Through this method, it is possible to restore or exceed the performance of the mold before damage, extend the service life of the mold, and reduce resource waste and production costs.
Smart Images

Figure CN119658186A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of laser processing of metal materials, and in particular relates to a high heat-resistant laser repair method for a failed mold. Background Art
[0002] The working environment of die-casting molds is very harsh. In addition to the strong friction caused by the flow of metal along the mold surface, the mold surface also undergoes repeated hot and cold cycles, forming thermal fatigue stress, causing mold failure. Mold failure is generally a local failure. If it is abandoned directly, it will cause a waste of resources. If a method can be used to repair the commonly damaged parts of the die-casting mold with laser to achieve or even exceed the performance before repair, it can greatly improve the performance and life of the die-casting mold, saving resources and production costs.
[0003] By using scrapped molds, nanoparticle-reinforced mold steel is developed. Trace nanoparticle-reinforced mold steel has unique innovations, does not change existing technical means, is green and environmentally friendly, and can achieve steel structure refinement and nano-precipitation phase refinement. Nanoparticles can be adsorbed at the front of the solid-liquid interface to hinder the growth of austenite dendrites. However, due to the large difference in specific gravity between nano-sized ceramic particles and molten steel, if the external addition method is used, it is easy to cause the aggregation of nanoparticles during the processing process. The use of the intermediate alloy method can avoid this problem. The nanoparticles are released during the laser additive process, so that the nanoparticles are evenly dispersed in the mold repair part. Therefore, nanoparticles are introduced into the scrapped mold body steel through the intermediate alloy method to repair the mold damaged by wear and thermal fatigue during the production process, so that its performance can be restored or exceed the performance before the mold is damaged. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention can be achieved through the following technical solutions:
[0005] A high heat-resistant laser repair method for a failed mold, the repair method comprising the following steps:
[0006] S1, Al powder, Ti powder and B4C are put into a ball mill and mixed evenly to obtain a mixed powder, which is then coated with aluminum foil, and a TiC+TiB2 / Al master alloy is obtained by pre-pressing and vacuum sintering;
[0007] S2, cutting the scrapped mold into pieces, putting them into an electric furnace for remelting, then adding the cut TiC+TiB2 / Al master alloy into the electric furnace to obtain molten steel, and injecting the molten steel into a ladle at a uniform speed, the nano-TiC+TiB2 particles are dispersed in the molten steel as the molten steel boils, and Al acts as a deoxidizer to generate aluminum oxides floating above the molten steel, and then pouring the molten steel into a sand mold to obtain nano-particle reinforced steel;
[0008] S3, heating the nanoparticle reinforced steel for start rolling, finishing rolling for 4-6 passes for spinning, collecting the wires after spinning, heating and annealing the collected wires to obtain trace nanoparticle reinforced die steel wires;
[0009] S4. Pre-treat the damaged mold to obtain a clean, crack-free surface, and then perform laser repair to obtain a mold repair embryo; then fine-process the embryo to obtain a repaired mold part.
[0010] Furthermore, in step S1, the mass ratio of Al powder, Ti powder and B4C is 24:6:70.
[0011] Furthermore, the content of TiC+TiB2 particles in the nano-particle reinforced steel is 0.04wt.%.
[0012] Furthermore, in step S3, the adding temperature of the nanoparticle reinforced steel is 950-1000°C, and the heating time is 2-3 minutes; the finishing rolling adopts a finishing mill, the finishing mill temperature is 890-900°C, and the spinning temperature is 830-860°C.
[0013] Furthermore, in step S3, the temperature at which the collected wires are heated is 600-650° C., and the heat preservation time is 2-3 hours.
[0014] Furthermore, the pretreatment in step S4 includes: cutting, grinding, cleaning, and drying, and the grinding thickness is guaranteed to be more than 2 mm.
[0015] Furthermore, the specific operation steps of the laser repair in step S4 are: a laser repair model is established according to the damaged part of the mold, and the laser repair system is operated by a robotic arm carrying a laser cladding nozzle. Under the combined action of laser and trace nanoparticle reinforced mold steel wire, multiple laser cladding passes are repeated to obtain a mold repair embryo.
[0016] Furthermore, the laser cladding parameters are as follows: laser power: 2500-3000 W; scanning speed: 0.2-0.7 m / min; wire feeding rate: 40-60 m / s; spot diameter: 2 mm.
[0017] A repaired mold part is prepared by the above-mentioned high heat-resistant laser repair method for a failed mold.
[0018] The beneficial effects of the present invention include: developing nanoparticle-reinforced steel for mold repair by using a damaged mold, introducing nanoparticles by using an intermediate alloy method, developing additive wires for mold repair with internally coated nanoparticles, and using the developed additive wires to perform laser additive repair on damaged areas of the mold damaged by wear and thermal fatigue during the production process, so that its performance can be restored to or exceed the performance before the mold was damaged. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0020] Figure 1 This is the preparation method of mold steel reinforced with trace nanoparticles in the embodiment.
[0021] Figure 2 Schematic diagram of laser repair in an embodiment.
[0022] Figure 3 Comparison of crack growth performance after 3000 hot-cold alternating fatigue cycles (a1-a4): laser repaired parts; (b1-b4)
[0023] Figure 4 The figure is a comparison of the thermal fatigue crack growth resistance of the laser repaired part in the embodiment and the quenched and tempered H13 steel.
[0024] Figure numerals: 1, hydraulic testing machine; 2, cold pressing block; 3, graphite mold; 4, vacuum sintering furnace; 5, medium frequency induction furnace; 6, molten steel; 7, ladle; 8, aluminum oxide; 9, TiC+TiB2 / Al master alloy; 10, nano-TiC+TiB2 particles; 11, sand mold; 12, nano-particle reinforced steel; 13, wire; 14, laser cladding nozzle; 15, laser; 16, damage to mold substrate DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Embodiment 1:
[0027] Designing Nanoparticle-Enhanced Powders:
[0028] To prepare the nanoparticle master alloy, Al powder, Ti powder and B4C were mixed in a mass ratio of 24:6:70, the mixed powder was put into a high-energy ball mill, and mixed evenly at a speed of 40 r / min for 48 hours, and the mixed powder was coated with aluminum foil.
[0029] Pre-pressing is performed on a hydraulic testing machine 1 to obtain a cold pressed block 2, which is then placed in a graphite mold 3 and heated in a vacuum sintering furnace 4 to undergo a combustion synthesis reaction, ultimately obtaining a TiC+TiB2 / Al intermediate alloy.
[0030] Cut the scrapped mold into blocks of 1kg-2kg and put them into the furnace of the medium frequency induction furnace for remelting. The pre-cut TiC+TiB2 / Al master alloy 9 is added to the medium frequency induction furnace 5 to obtain molten steel 6. When the steel is tapped at a temperature of about 1650°C, the molten steel 6 is uniformly injected into the ladle 7 at about 1500°C. The nano-TiC+TiB2 particles 10 are dispersed in the molten steel as the molten steel boils. Al acts as a deoxidizer to generate aluminum oxide 8 floating above the molten steel. The molten steel is then poured into the sand mold 11 to obtain nano-particle reinforced steel 12.
[0031] Preparation of Nanoparticle Reinforced Die Steel Wire:
[0032] The obtained nanoparticle reinforced steel is placed in the furnace of a medium frequency induction furnace, and the nanoparticle reinforced die steel is heated to 950°C and maintained for 2 minutes before rolling. The temperature of the finishing mill is 890°C. The finishing rolling is performed for 4-6 passes to produce wire at a temperature of 830°C. The wire is collected after the wire is produced. The collected wire is heated to 600°C and kept warm for 2 hours to obtain the trace nanoparticle reinforced die steel wire after annealing.
[0033] The damaged parts of the mold are cut, polished, cleaned, dried and polished to a thickness of more than 2mm. After obtaining a clean and crack-free surface, laser repair is performed.
[0034] A laser repair model is established according to the damaged part of the mold. The laser repair system is operated by a robotic arm carrying a laser cladding nozzle 14. For the damaged mold substrate 16, the selected laser cladding parameters are laser power: 2500W, scanning speed: 0.2m / min, powder feeding rate: 40m / s, spot diameter 2mm. According to the different selected laser cladding parameters, such as Figure 2 As shown, the cladding area can obtain different properties. Under the joint action of the laser 15 and the wire 13, after repeated laser cladding, a mold repair embryo is obtained. The added material part exceeds the original size of the mold by 2-3mm. After polishing, the original size and shape of the mold are restored and it can continue to be used.
[0035] At the same time, in order to study the anti-cold and hot alternating fatigue performance of the mold repair area and the common mold manufacturing steel H13 steel on the market, we cut the test sample into small pieces of 35×25×5mm using wire cutting, and prefabricated a 6×0.15mm crack in the middle of the experiment. The experiment was carried out on a homemade hot and cold fatigue alternating test machine. The sample was hung on a steel rod, and when it was heated to the required temperature of 600℃, it was kept warm for 5 minutes, and then the motor was turned on to control the sample to rise and fall in the heating furnace and cooling circulating water. The heating furnace was kept warm for 3 minutes, and the cooling in the cooling circulating water was cooled for 20 seconds as one cycle.
[0036] This cycle is repeated 3000 times, and the final fatigue resistance to alternating hot and cold is as follows: Figure 3 As shown in the figure. After 3000 hot and cold alternating fatigue cycles (20℃-550℃), the surface oxidation erosion of the laser repaired part and the H13 steel after quenching and tempering. The surface of the sample was analyzed by energy spectrum element scanning, and it can be seen that the area of oxidation erosion of the quenched and tempered H13 steel is significantly higher than that of the laser repaired part.
[0037] Embodiment 2:
[0038] A laser repair method for failed molds with high resistance to thermal cracking:
[0039] Designing Nanoparticle-Enhanced Powders:
[0040] To prepare the nanoparticle master alloy, Al powder, Ti powder and B4C were mixed in a mass ratio of 24:6:70, the mixed powder was put into a high-energy ball mill, and mixed evenly at a speed of 40 r / min for 48 hours, and the mixed powder was coated with aluminum foil.
[0041] Pre-pressing is performed on a hydraulic testing machine 1 to obtain a cold pressed block 2, which is then placed in a graphite mold 3 and heated in a vacuum sintering furnace 4 to undergo a combustion synthesis reaction, ultimately obtaining a TiC+TiB2 / Al intermediate alloy.
[0042] Cut the scrapped mold into blocks of 1kg-2kg and put them into the furnace of the medium frequency induction furnace for remelting. The pre-cut TiC+TiB2 / Al master alloy 9 is added to the medium frequency induction furnace 5 to obtain molten steel 6. When the steel is tapped at a temperature of about 1650°C, the molten steel 6 is uniformly injected into the ladle 7 at about 1500°C. The nano-TiC+TiB2 particles 10 are dispersed in the molten steel as the molten steel boils. Al acts as a deoxidizer to generate aluminum oxide 8 floating above the molten steel. The molten steel is then poured into the sand mold 11 to obtain nano-particle reinforced steel 12.
[0043] Preparation of Nanoparticle Reinforced Die Steel Wire:
[0044] The obtained nanoparticle reinforced steel is placed in the furnace of a medium frequency induction furnace, and the nanoparticle reinforced die steel is heated to 1000°C and maintained for 2 minutes, and then rolled, and the temperature of the finishing mill is 900°C; the finishing rolling is performed for 4-6 passes to produce wire, and the wire-producing temperature is 860°C; the wire is collected after the wire-producing. The collected wire is heated to 600°C and kept warm for 2 hours to obtain the trace nanoparticle reinforced die steel wire after annealing.
[0045] The damaged parts of the mold are cut, polished, cleaned, dried and polished to a thickness of more than 2mm. After obtaining a clean and crack-free surface, laser repair is performed.
[0046] A laser repair model is established according to the damaged part of the mold. The laser repair system is operated by a robotic arm carrying a laser cladding nozzle 14. For the damaged mold substrate 16, the selected laser cladding parameters are laser power: 3000W, scanning speed: 0.7m / min, powder feeding rate: 60m / s, spot diameter 2mm. According to the different selected laser cladding parameters, such as Figure 2 As shown, the cladding area can obtain different properties. Under the joint action of the laser 15 and the wire 13, after repeated laser cladding, a mold repair embryo is obtained. The added material part exceeds the original size of the mold by 2-3mm. After polishing, the original size and shape of the mold are restored and it can continue to be used.
[0047] At the same time, in order to study the high-temperature friction and wear properties of the mold repair area and the common mold manufacturing steel H13 steel on the market, the test sample was made into a round rod with a size of Φ6×14mm, and the upper and lower surfaces were ensured to be parallel. The surface involved in the wear was polished after being ground smooth, and a high-temperature friction and wear experiment was carried out. The wear conditions were set as temperature 450℃, load 10N, rotation speed 300r / min, and wear time 30min.
[0048] The final high temperature friction and wear performance is as follows Figure 4 As shown. Figure 4 (a) It can be seen that when the load is 10N, there are wear debris and fine oxide dots on the wear surface of the mold steel at the laser repaired part, which indicates that the wear mechanism at this time is mainly adhesive wear and abrasive wear. Figure 4 (b) It can be seen that there are obvious plowing grooves and a small amount of wear debris on the surface of the quenched and tempered H13 steel, which indicates that the wear mechanism at this time is mainly plowing wear and adhesive wear. Figure 4 (c) It can be seen that the surface of the mold steel sample at the laser repair site shows adhesive wear. The surface of the sample is relatively flat, the maximum furrow depth is 3.6μm, and the furrow width is small. Figure 4(d) The surface of the quenched and tempered H13 steel sample shows severe plowing wear, with a maximum plowing groove depth of 4.4 μm. At the same time, the plowing groove width of the quenched and tempered H13 mold steel is larger than the plowing groove width of the mold steel in the laser repaired area. The high temperature wear resistance of the mold steel in the laser repaired area is better than that of the quenched and tempered H13 steel.
[0049] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0050] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A high heat-resistant laser repair method for a failed mold, characterized in that: The repair method comprises the following steps: S1, Al powder, Ti powder and B4C are put into a ball mill and mixed evenly to obtain a mixed powder, which is then coated with aluminum foil, and a TiC+TiB2 / Al master alloy is obtained by pre-pressing and vacuum sintering; S2, cutting the scrapped mold into pieces, putting them into an electric furnace for remelting, then adding the cut TiC+TiB2 / Al master alloy into the electric furnace to obtain molten steel, and injecting the molten steel into a ladle at a uniform speed, the nano-TiC+TiB2 particles are dispersed in the molten steel as the molten steel boils, and Al acts as a deoxidizer to generate aluminum oxides floating above the molten steel, and then pouring the molten steel into a sand mold to obtain nano-particle reinforced steel; S3, heating the nanoparticle reinforced steel for start rolling, finishing rolling for 4-6 passes for spinning, collecting the wires after spinning, heating and annealing the collected wires to obtain trace nanoparticle reinforced die steel wires; S4. Pre-treat the damaged mold to obtain a clean, crack-free surface, and then perform laser repair to obtain a mold repair embryo; then fine-process the embryo to obtain a repaired mold part.
2. The high heat resistance laser repair method for failed mold according to claim 1 is characterized in that: In step S1, the mass ratio of Al powder, Ti powder and B4C is 24:6:
70.
3. The high heat resistance laser repair method for failed mold according to claim 1 is characterized in that: The content of TiC+TiB2 particles in the nanoparticle reinforced steel is 0.04wt.%.
4. The high heat resistance laser repair method for failed mold according to claim 1 is characterized in that: In step S3, the nanoparticle reinforced steel is added at a temperature of 950-1000°C and the heating time is 2-3 minutes; the finishing rolling adopts a finishing mill, the finishing mill temperature is 890-900°C, and the spinning temperature is 830-860°C.
5. The high heat resistance laser repair method for failed mold according to claim 1 is characterized in that: In step S3, the temperature of heating the collected wire material is 600-650° C. and the heat preservation time is 2-3 hours.
6. The high heat resistance laser repair method for failed mold according to claim 1 is characterized in that: The pretreatment in step S4 includes: cutting, grinding, cleaning, and drying, and the grinding thickness is guaranteed to be more than 2 mm.
7. The high heat resistance laser repair method for failed mold according to claim 1 is characterized in that: The specific operation steps of laser repair in step S4 are: a laser repair model is established according to the damaged part of the mold, and the laser repair system is operated by a robotic arm carrying a laser cladding nozzle. Under the combined action of laser and trace nanoparticle reinforced mold steel wire, multiple laser cladding passes are repeated to obtain a mold repair embryo.
8. The high heat resistance laser repair method for failed mold according to claim 1 is characterized in that: Laser cladding parameters selection: laser power: 2500-3000W; scanning speed: 0.2-0.7m / min; wire feeding rate: 40-60m / s; spot diameter: 2mm.
9. A repaired mold part is prepared by the high heat-resistant laser repair method for a failed mold as described in any one of claims 1 to 8.
Citation Information
Patent Citations
Method for adopting laser fuse wires for repairing mold
CN103521923A
Smelting process for steel for low-silicon aluminum steel-free welding wire
CN105132621A
Wear-resistant and antifriction metal-ceramic composite coating process for hot-work die steel
CN106191853A
Self-reaction flux-cored wire for wear-resisting coating and preparation and application of self-reaction flux-cored wire
CN106624426A
Metal powder for repairing H13 die steel for laser cladding
CN107164756A